Dual crosslinked injectable protein-based hydrogels with cell anti-adhesive properties. (1st March 2023) - Giri, Pijush; Verma, Devendra
Abstract: Currently, one of the most severe clinical concerns is post-surgical tissue adhesions. Using films or hydrogel to separate the injured tissue from surrounding tissues has proven the most effective method for minimizing adhesions. Therefore, by combining dual crosslinking with calcium ions (Ca 2+ ) and tetrakis(hydroxymethyl) phosphonium chloride, we were able to create a novel, stable, robust, and injectable dual crosslinking hydrogel using albumin (BSA). This dual crosslinking has preserved the microstructure of the hydrogel network during the degradation process, which contributes to the hydrogel's mechanical strength and stability in a physiological situation. At 60% strain, compressive stress was 48.81 kPa obtained. It also demonstrated excellent self-healing characteristics (within 25 min), tissue adhesion, excellent cytocompatibility, and a quick gelling time of 27 ± 6 s. Based on these features, the dual crosslinked injectable hydrogels might find exciting applications in biomedicine, particularly for preventing post-surgical adhesions.